Analisis Perbandingan Proporsi Pengeluaran Pangan dan Tingkat Kecukupan Energi dan Protein Berdasarkan Konsep Pengukuran Ketahanan Pangan pada Rumah Tangga Program dan Rumah Tangga Non-Program Kawasan Mandiri Pangan di Kecamatan Seulimeum Kabupaten Aceh Besar - Naufal Mutawakkil; Elly Susanti; Safrida Safrida (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Based on the concept of measuring food security at the household level, a high proportion of food expenditure from total expenditure is an indication of a low level of food security. The same variable can be seen from the level of calory and protein adequacy, where if the level of adequacy is below the recommended consumption based on the adequacy rate, the household is indicated to be experiencing food insecurity. This research is a cross sectional study by comparing the proportion of food expenditure, calory and protein adequacy levels between two groups of respondents, namely households that have become program recipients and have entered their fourth year with households that are not program participants. The results of the study indicate that most of the household expenditure levels in the recipient group (86.7%) and non-recipient group (73.3%) are included in the category of low food expenditure proportion level, which means that the two groups of respondents from the food expenditure dimension are mostly classified as good. Most of the household energy adequacy level in the recipient group is in the sufficient category (56.7%), while the non-recipient households are mostly in the less category (60.0%). The level of protein consumption of the two groups of beneficiary and non-recipient households is mostly in the less category with values of 63.3% and 76.7%. The results of the Mann-Whitney test showed that there was a significant difference between the percentage of food expenditure in the two groups (P value = 0.000), while the calory and protein consumption level variables there was no significant difference in the two groups with a significance value of each P value = 0.074 and P = 0.115.